(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The essay pursuits to show, by means of an examination of art 445 of the Spanish criminal code, the solution that the Spanish criminal system gives to a phenomenon as frequent and harmful as it is corruption within international economic transactions. This issue, object of attention of international organisations (UNO, OECD,EU…), constitutes one of the most burning issues of today criminal policy.